Resonant tunneling diode photodetectors for optical communications - Rodrigues, Gil C. (2018)
Resonant tunneling diodes (RTDs) have been extensively studied due to their potential applications in very high speed electronics, optical communications, and terahertz generation. In this work, we report the latest results on the characterization of the resonant tunneling diode photo-detectors (RTD-PDs), incorporating InGaAlAs light sensitive layers for sensing at the telecommunication wavelength of lambda = 1310 nm. We have measured responsivities up to 28.8 A/W and light induced voltage shift of 204.8 V/W for light injection powers around 0.25 mW.